Probabilistic Analysis of the accumulated hotspot occurred during January to April 2016 with generalized extreme value distribution method - มงคลงาม กิตติพล; แถวถาทำ ศศิประภา (Journal of Applied Statistics and Information Technology, 2016)
Thailand presently faces problems with forest fire damage to its natural resources and economic. The hotspot monitoring with remote sensing technology is significant for forest fire protection. The probabilistic analysis of the accumulated hotspot occurred with generalized extreme value distribution method is used for hotspot monitoring during January to April 2016. Finding revealed that a maximum of hot spot during April 2016 in North Region in conservative forest is 5,933 points, Central Region in conservative zones is 436 points, Northeast Region in agriculture zone is 2,209 points, and South Region in agriculture zone is 89 points, From the forest fire statistics, the agriculture and the forest areas being occurred the forest fire should be monitored. Thus, they are consistent with the observed data, to be accredited with this research, it is used for the hotspot monitoring efficiently.